Adaptive designs for phase I trials 2 - Ivanova, Anastasia (Henry Stewart Talks, 2016)
Continual Reassessment Method (CRM), Dose-finding designs for trials with delayed outcome, Designs for dose-finding trials with multiple agents & ordered subpopulations